Tamoxifen differentially regulates miR-29b-1 and miR-29a expression depending on endocrine-sensitivity in breast cancer cells. (1st March 2017) - Muluhngwi, Penn; Krishna, Abirami; Vittitow, Stephany L.; Napier, Joshua T.; Richardson, Kirsten M.; Ellis, Mackenzie; Mott, Justin L.; Klinge, Carolyn M.
Abstract: Endocrine-resistance develops in ∼40% of breast cancer patients after tamoxifen (TAM) therapy. Although microRNAs are dysregulated in breast cancer, their contribution to endocrine-resistance is not yet understood. Previous microarray analysis identified miR-29a and miR-29b-1 as repressed by TAM in MCF-7 endocrine-sensitive breast cancer cells but stimulated by TAM in LY2 endocrine-resistant breast cancer cells. Here we examined the mechanism for the differential regulation of these miRs by TAM in MCF-7 versus TAM-resistant LY2 and LCC9 breast cancer cells and the functional role of these microRNAs in these cells. Knockdown studies revealed that ERα is responsible for TAM regulation of miR-29b-1/a transcription. We also demonstrated that transient overexpression of miR-29b-1/a decreased MCF-7, LCC9, and LY2 proliferation and inhibited LY2 cell migration and colony formation but did not sensitize LCC9 or LY2 cells to TAM. Furthermore, TAM reduced DICER1 mRNA and protein in LY2 cells, a known target of miR-29. Supporting this observation, anti-miR-29b-1 or anti-miR-29a inhibited the suppression of DICER by 4-OHT. These results suggest miR-29b-1/a has tumor suppressor activity in TAM-resistant cells and does not appear to play a role in mediating TAM resistance. Highlights: Tamoxifen-ERα inhibits pri-miR-29b-1/a transcription in MCF-7 cells, but stimulates transcription in endocrine-resistant cells. miR-29b-1 and miR-29a inhibit MCF-7, LCC9, and LY2 cell proliferation and LY2 migration and colony formation. Inhibition of miR-29b-1/a does not sensitize LCC9 and LY2 cells to tamoxifen. Tamoxifen acting through ERα represses DICER1 by increasing miR-29b-1/a in LY2 cells. Tamoxifen-induced miR-29b-1/a may be involved in endocrine sensitivity, not resistance.